(untitled) (AMJ (Advanced Medical Journal), 2022)
Background and Objectives Thyroid diseases and Diabetes are the most common endocrinal disorders seen in clinical practice. As a result, it is common for an individual to be affected by both thyroid diseases and diabetes. Most studies show an increased incidence of thyroid dysfunction in type 2 DM than in the general population. The unrecognized thyroid dysfunction not only worsens metabolic control but also impedes the management of diabetes. The aim of this study is to estimate the frequency and characteristics of thyroid dysfunction among type-2 diabetic patients in Duhok Governorate. Patients and Methods The study population consisted of a total 101 randomly sample Type II diabetic patients from 1st January to 30th November 2013 at Duhok Diabetic center. The patients were interviewed and examined, and their blood samples were taken for lipid profiles, Thyroid function tests, and at least 2 fasting blood sugars were checked. Results The study population consisted of a total of 101 Type II diabetic patients (33 males and 68 females) with a mean age of 53.73± 9.07 and 51.97± 11.93respectively. 74 out of 101 patients were euthyroid. The remaining 27 patients had thyroid dysfunction. Subclinical hypothyroid is commonest 14.9% followed by overt hypothyroidism constituting 7.9%. Conclusions Thyroid dysfunction is common among Type 2 DM and it is more common in females than males. Of thyroid dysfunction, subclinical hypothyroidism was the most common type followed by overt hypothyroidism. Dyslipidemia was significantly higher in the hypothyroid group than in the euthyroid group specifically atherogenic LDL. Glycemic control was poor significantly in hypothyroid and hyperthyroid groups than in euthyroid so unidentified thyroid dysfunction could negatively impact glycemic control.